KEPEMIMPINAN KEPALA SEKOLAH DAN PROFESIONALISME GURU BAHASA ARAB PESANTREN DI KOTA LHOKSEUMAWE - Salsabila, Aina (At- Tarbawi, 2020)
In a number of junior high schools based on the Islamic boarding school in Lhokseumawe city do not have Arabic teachers with educational backgrounds according to their fields of expertise, this will affect the professionalism of teachers in teaching Arabic subjects. The purpose of this study was to explain the leadership style of  principal?s Junior High School (MTsS) in carrying out their duties, to descripe the professionalism of  Arabic  Junior high School (MTsS) teachers in carrying out their duties and to know the influence of principal leadership style on the professionalism of  Arabic Junior High School teachers in Islamic boarding school in Lhokseumawe City. The method used  is a survey method with a quantitative approach, the sample is 27 respondents. Data analyzes using simple linear regression. The results showed that 81% (22 teachers) favored the principal's leadership style and 70% (19 Arabic language teachers) were able to develop their professional competencies. Simple linear regression test results show the significance value for the influence of  X on Y is 9,308> 2,055, thus there is a significant influence of school leadership on the professionalism of Arabic MTsS Islamic boarding School teachers in Lhokseumawe, then H0is rejected and Ha is accepted. From the data analysis it was found that the performance of  the MTsS Islamic Boarding School principals in Lhokseumawe was already good, the majority of school principals understood their managerial duties in managing schools and directing Arabic language teachers to improve their competence, but the level of teachers professionalism was not it is only influenced by external factors (principal's leadership) but is also greatly influenced by internal factors such as self-motivation and teacher competencies.